The laser ablation model development of glass substrate cutting assisted with the thermal fracture and ultrasonic mechanisms. (April 2015) - Huang, Kuo-Cheng; Hsiao, Wen-Tse; Hwang, Chi-Hung; Lin, Ru-Li; Andrew Yeh, Jer-Liang
Abstract: This study presents three hybrid processing models for cutting a glass substrate, and compares their cutting speeds. The three models are (I) thermal fracture cutting technology (TFCT)-assisted laser ablation, (II) ultrasonic-assisted laser ablation, and (III) ultrasonic and TFCT-assisted laser ablation. In the experiment, a 12 W 355 nm Nd:YVO4 laser system, a 40 W CO2 laser and an ultrasonic transducer were used to cut 3 mm thick soda-lime glasses. Lasers and ultrasonic transducers were used as heat sources and vibration sources, respectively. Results show that the surface morphology of the soda-lime glass sheet depends on the processing models. After cutting, the surface and cross-sectional morphology of glass substrate were observed using a portable digital microscope and residual stresses were also evaluated thanks to a photoelasticity instrument. Highlights: Three hybrid processing derived from the TFCT method used to cut soda lime glass. The study is based on the SIF of fracture mechanics, fatigue and weight function theories. UV, CO2 lasers and a vibration source are combined for cleavage of glasses. The new processes have faster speeds and higher cutting qualities than TFCT.